Analysis of Traveller Perceptions and Expectations on Staycation Activities in Cisaat SubangTourist Village West Java in the New Normal Period - Nurlaila; Laras, Prastiti; Suparno, Fajar (International Journal of Travel, Hospitality and Events, 2022)
Purpose: The purpose of this study is to analyze changes in tourist perceptions and expectations in Staycation activities in the Cisaat Subang tourist village, West Java in the new normal period. Research methods: This study uses a descriptive qualitative approach to analyze changes in the perceptions and expectations of tourists in the Tourist Village of Cisaat Subang, from normal to post-pandemic or the new normal period. The respondents taken were 10 tourists who had visited the tourist village of Cisaat Subang, West Java. Results and discussion: Through the analysis carried out, the results of the perceptions and expectations of tourists have changed along with the pandemic that occurs. Implication: The tourists agree that they want improvements and additional facilities that support them to vacation there, especially after the Covid-19 pandemic as a guarantee of safety and comfort for them vacationing in the tourist village of Cisaat Subang, West Java in this new normal period.   Keywords: perceptions and expectations of tourists, staycation, cisaat subang tourism village.